Rn-222, Rn-220 and other dissolved gases in mineral waters of southeast Brazil - Bonotto, Daniel Marcos (Elsevier B.V., 2014)
This paper describes the natural radioactivity due to Rn-222 and Rn-220 in mineral waters occurring at Sao Paulo and Minas Gerais states, Brazil, that are extensively used for drinking in public places, bottling and bathing purposes, among other. The measurements of these alpha-emitting radionuclides were also accompanied by the monitoring of temperature and some dissolved gases (O-2, CO2 and H2S) in 75 water sources located in 14 municipalities of those states. Eight water sources yielded Rn-220 activity concentration values below the detection limit of 4 mBq/L On other hand, Rn-222 activity concentration values exceeding the WHO guidance level of 100 Bq/L in drinking-water for public water supplies were found in two springs, named Villela and Dona Beja, whose discharge occurs in areas characterized by the presence of enhanced levels of natural radioelements in rocks. The obtained results were compared with the guidelines of the Brazilian Code of Mineral Waters (BCMW) that was established in 1945 and is still in force in the country. The Rn-222 and Rn-220 activity concentration data allowed perform dose radiation calculations based on the potential alpha energy concentration (PAEC), whose implications for health risk have been also considered in this paper. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Radon and thoron; Mineral waters; Dissolved gases; Radiation dose